যদি \(\cfrac{ay−bx}{c}=\cfrac{cx−az}{b}=\cfrac{bz−cy}{a}\) হয়, তবে প্রমাণ করো \(\cfrac{x}{a}=\cfrac{y}{b}=\cfrac{z}{c}\) Madhyamik 2020 , 2003


\(\cfrac{ay-bx}{c}=\cfrac{cx-az}{b}=\cfrac{bz-cy}{a}\)
∴ \(\cfrac{c(ay-bx)}{c^2} =\cfrac{b(cx-az)}{b^2} =\cfrac{a(bz-cy)}{a^2}\)
\(=\cfrac{c(ay-bx)+b(cx-az)+a(bz-cy)}{c^2+b^2+a^2}\)

[সংযোজন পক্রিয়া করে পাই]

\(=\cfrac{acy-bcx+bcx-abz+abz-acy}{a^2+b^2+c^2}\)
\(=0\)

সুতরাং,\(\cfrac{ay-bx}{c}=0\)
বা, \(ay-bx=0\)
বা, \(ay=bx ∴ \cfrac{y}{b}=\cfrac{x}{a}\)

আবার, \(\cfrac{cx-az}{b}=0\)
বা, \(cx-az=0\)
বা, \(cx=az ∴ \cfrac{x}{a}=\cfrac{z}{c}\)

\(∴ \cfrac{x}{a}=\cfrac{y}{b}=\cfrac{z}{c}\) (প্রমাণিত)


Similar Questions